Tinjauan Pengaruh Kualitas Genteng BetonDengan Bahan Tambah Serbuk Gergaji Kayu Jati - Nugroho, Aditya Prima, Ir, Ali Asroni, M.T (2016)
Development in modern times today, a lot of people vying to innovate as well as concrete tile. Concrete tile is a new innovation in the world of development . concrete tile roof has a function as a cover, but the concrete tile has a heavy weight when compared to other tiles and are more expensive. This study aims to determine the effect of the quality of the concerte tile with the added material teak sawdust, the quality of the concrete tile reviewed against bending loads, water seepage, water absorption, nature seemed, the same of size and heat absorption. Ratio of the mixture used is 1 cement : 2 lime mill : 2,5 sand and variations addition of teak sawdust by 0%; 5%; 10%; 15% and 20% of the weight of the sand. The study was conducted at the laboratory of Civil Engineering Building Materials Universitas Muhammadiyah Surakarta. Bending load test result an average of concerte tile on the addition of teak sawdust 0% = 116,23 kg; 5% = 130,64 kg; 10% = 137,36 kg; 15% = 144,09 kg and 20% = 149,85 kg. the result of water seepage on all variations off the concerte tile is note experiencing seepage. The test result of average water absorption of concerte roof tiles in the addition of teak sawdust 0% = 6,99%; 5% = 5,15%; 10% = 6,38%; 15% = 5,08% and 20% = 7,44%. The test results seemed properties of concrete roof tiles with all the variations have smooth surface, elbow and not cracked, just a few on the variations of 0%; 10% and 20% there is a cavity. The same of size result the average size of the concrete tile P = 420 mm , L = 335 mm , thick sections average = 14,06 mm, thickness passenger = 8,5 mm, connection length = 420 mm, connection width = 12,5 mm, hight hook = 15,42 mm , width passenger = 78 mm, groove depth = 34,5 mm. Heat absorption test result average variation of the addition of teak sawdust 0% = 86,07 %; 5% = 86,44%; 10% = 82,68%; 15% = 85,50% and 20% = 82,12%. Of the test results, we conclude that the more percentage of sawdust teak adding in concrete tile, the greater the bending load is generated. The results of this research on testing resilience against seepage, water absorption, nature looks and size have met the requirements SNI 0096-2007, while research on bending loads and heat absorption has not met.